Pemberdayaan Kader “BERSERI” (Bersih, Sehat, Mandiri) untuk Meningkatkan PHBS dan Ekonomi Keluarga di Desa Adat Baduy - Handayani Tarigan, Gita; Samira, Jihan; Armas, Anita; Fatimah Sulenra, Ayu; Hambawan, Tulus; Akmal Faujan Juarsa, Muhammad (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2025)
Clean and Healthy Living Behavior (CHLB) is a main foundation to achieve an optimal level of public health through the adoption of healthy lifestyle practices in daily life. In indigenous communities such as the Baduy, the implementation of CHLB faces challenges, particularly related to culture, beliefs, and access to healthcare services. This community service program provided education and training for women’s groups in the Baduy community to improve the application of household CHLB and enhance family economic resilience. The target participants were Baduy women organized in the “BERSERI” (Clean, Healthy, Independent) cadre group. Health education on household CHLB in this program had a statistically significant impact on increasing participants’ knowledge (p<0.05). Furthermore, participants were trained in entrepreneurship and the development of Baduy woven products, resulting in agenda books and purses. The development of Baduy weaving products contributes to improving community welfare through entrepreneurship and economic empowerment in the Baduy community.